Destino de frações minerais do nitrogênio (15N) em reservatórios do solo afetado pelo tipo de preparo: experimento de longa duração em Botucatu, SP - Callegari, Gustavo Prezotto (Universidade Federal de São Carlos, 2025)
The intensification of agriculture demands improved nutrient use efficiency, particularly for nitrogen (N), which is essential for plant growth but highly prone to environmental losses. In this context, understanding N dynamics in the soil is fundamental for the development of more sustainable management systems. The choice between conventional tillage (CT) and no-till (NT) can significantly influence N transformation and retention processes, due to their contrasting effects on soil structure, microbial activity, and organic matter. This study aimed to evaluate N dynamics in soil under CT and NT systems, using nitrate- and ammonium-based forms of N as tracers, applied through fertilizers enriched with the stable isotope ¹⁵N. The focus was not on the agronomic performance of the N sources themselves, but rather on their role as tools to trace the fate of N in the soil under different management systems. The experiment was conducted in a randomized block design with a 2×3×7 factorial scheme, being two management systems (SD and PC), three N sources [control – without N, ammonium [(¹⁵NH₄)₂SO₄] and nitrate (K¹⁵NO₃)] and seven evaluation times evaluation (0, 2, 6, 12, 20, 30, and 42 days after the application of nitrogen sources). Soil samples were incubated in the laboratory and analyzed for total nitrogen (TN), mineral nitrogen (MN), total organic nitrogen (TON), pH, and ¹⁵N isotopic abundance. Results showed that CT promoted faster incorporation of fertilizer N into the soil, with a 21% higher contribution of nitrogen derived from the fertilizer (Ndff) in the total N pool. However, N losses were 38% greater with the ammonium source compared to the nitrate source under CT. In contrast, NT presented 21% higher concentrations of total and organic N, indicating a greater accumulation and long-term retention of nitrogen. It was concluded that, although CT facilitates faster N incorporation, NT is more effective in building and conserving soil N pools, contributing to agro-environmental sustainability. The isotopic technique was essential to elucidate these dynamics, highlighting the critical role of management systems and N forms in fertilization efficiency and mitigation of environmental losses.
Fate of mineral nitrogen (¹⁵N) fractions in soil reservoirs affected by tillage system: a long-term experiment in Botucatu, SP
Keywords: Eficiência do uso de nitrogênio; Fertilizantes; Frações de N do solo; Plantio direto; Plantio convencional; Nitrogen use efficiency; Fertilizers; Soil N fractions; No-tillage; Conventional tillage; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO